Pharmacokinetic Drug‐Drug Interactions Between Trospium Chloride and Ranitidine Substrates of Organic Cation Transporters in Healthy Human Subjects. (22nd September 2019) - Abebe, Bayew Tsega; Weiss, Michael; Modess, Christiane; Tadken, Tobias; Wegner, Danilo; Meyer, Marleen J.; Schwantes, Ulrich; Neumeister, Claudia; Scheuch, Eberhard; Schulz, Hans‐Ulrich; Tzvetkov, Mladen; Siegmund, Werner
Abstract: Trospium chloride, a muscarinic receptor blocker, is poorly absorbed with different rates from areas in the jejunum and the cecum/ascending colon. To evaluate whether organic cation transporter (OCT) 1, OCT2 and multidrug and toxin extrusion (MATE) 1 and MATE2‐K are involved in pharmacokinetics, competitions with ranitidine, a probe inhibitor of the cation transporters, were evaluated in transfected HEK293 cells. Furthermore, a drug interaction study with trospium chloride after intravenous (2 mg) and oral dosing (30 mg) plus ranitidine (300 mg) was performed in 12 healthy subjects and evaluated by noncompartmental analysis and population pharmacokinetic modeling. Ranitidine inhibited OCT1, OCT2, MATE1, and MATE2‐K with half maximal inhibitory concentration values of 186 ± 25 µM, 482 ± 105 µM, 134 ± 37 µM, and 35 ± 11 µM, respectively. In contrast to our hypothesis, coadministration of ranitidine did not significantly decrease oral absorption of trospium. Instead, renal clearance was lowered by ∼15% (530 ± 99 vs 460 ± 120 mL/min; P  < .05). It is possible that ranitidine was not available in competitive concentrations at the major colonic absorption site, as the inhibitor is absorbed in the small intestine and undergoes degradation by microbiota. The renal effects apparently result from inhibition of MATE1 and/or MATE2‐K by ranitidine as predicted by in vitro to in vivo extrapolation. However, all pharmacokinetic changes were not of clinical relevance for the drug with highly variable pharmacokinetics. Intravenous trospium significantly lowered mean absorption time and relative bioavailability of ranitidine, which was most likely caused by muscarinic receptor blocking effects on intestinal motility and water turnover.